A Comparative Study of Respiratory Activity of Tropical Products under Two Storage Conditions - Nugraha, Bayu; Rahmah, An-Nidaa' Fatkhur; Ayuningsih, Ira; Priyanti, Devi; Affandi, Fahrizal Yusuf (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
This study aimed to investigate respiration process of Indonesian tropical products and its parameter to support the use of CAS. Shallot, dragon fruit and sneak fruit that are high-value and export-potential products in Indonesia were investigated. For respiration measurement, the fruits were kept in tightly closed jars. The ratio of fruit volume and free volume of jar (headspace) was determined to calculate the rate of fruit respiration. To observe the storage condition effects, the jars were stored in two different temperatures: low temperature (7±2°C) and room temperature (27±2°C). In cold temperature storage, changes in O2 and CO2 concentrations are slower than in room temperature storage. The rate of O2 consumption and CO2 production of products during storage decreased as the O2 concentration decreased for all conditions. Based on the dramatic increase of RQ value at low O2 concentrations, the low oxygen limits (LOLs) of shallot, sneak fruit and dragon fruit were estimated at around 7.5%, 4% and 2% O2 respectively, at the room temperature. However, the LOL was not detected yet at a cold temperature for 200 h of measurement due to a slow decrease of O2. The results showed that different products had different respiration activities so that the storage procedures should be different. A determination of model-based LOL and validation would be needed in the next research to be precisely applied on CAS. Keywords: Carbon dioxide, Dragon fruit, Shallot, Oxygen, Postharvest, Snake fruit.